THE NEEDS ANALYSIS OF MULTILINGUAL THEMATIC DIGITAL DICTIONARY FOR LITERACY DEVELOPMENT - Dewi, Ni Putu Desy Krisna; Ratminingsih, Ni Made; Budasi, I Gede (E-Link Journal, 2023)
Students must be capable of technological advances that can make it easier to interact and compete in the world in the digital age. Therefore, students must have a strong foundation following the desired needs and achievements concerning English language skills. One of the supporting students' learning is a digital dictionary with multilingual. Thus, this study aims to develop a multilingual digital dictionary for fifth-grade elementary school students. However, this article describes the need for multilingual Digital dictionaries for fifth-grade elementary school students. This study involved 656 students and 27 English Teachers in grade five from Nine sub-districts in Buleleng Regency. This qualitative research aimed to analyze the results of needs for, In data capture. The study used observations, questionnaires, and interviews. This study shows that students are in dire need and want a multi-lingual digital dictionary to support their English learning.Â